Materials, Capital, Direct/Indirect Substitution and Mass Balance Production Functions - Jeroen C.J.M. van den Bergh (Tinbergen Institute, 1998)
A foundation is provided for a correct and accurate analysis of the relationship between monetary values and physical dimensions in economic production. A distinction is proposed between direct and indirect substitution. Linked to this, a classification is offered of various types of substitutability and complementarity relationships between production factors. It is argued that the neoclassical production function may be consistent with mass balance, but is unsuitable for a detailed and accurate understanding of changes in production that influence materials use. For this purpose, general production functions satisfying mass balance are formulated, drawing upon the proposed classifications.
Keywords: 330; Production; Production functions; Substitution; Economics; Recycling; Economic models; Functions; Demand; Produktionsfunktion; Theorie